Existing Practicies of Parent-child Communication on Sex-related Matters among Households in Ondo State, Nigeria - Oyewole Olusanya; Ayodele Jegede (European Scientific Journal, ESJ, 2022)
Adolescents' sexual and reproductive health remain global public health concerns particularly in Sub-Saharan. Undoubtedly, parent-child communication remains a vital means by which parents transmit cultural values and monitor the sexual health of their children. The nature and the quality of sexual conversations that subsist in the family are critical factors in the prevention of sexual risk-taking behaviour among adolescents. Therefore, this paper investigated the existing practices of parent-child communication on sex-related matters among households in Ondo State among the triads of parents and their adolescent children and the implications for adolescents’ sexual health in Ondo State, Nigeria. The study elicited data from 483 respondents comprising fathers, mothers and their adolescents; through a multi-stage sampling technique. First, the study found that for most of the respondents (fathers 56.5%, mothers 54.7% and adolescents 60.2%) sexual conversations are occasional; second, mothers often initiate sex-related discussion with children more than fathers; third, sexual conversations are generally not open and receptive; fourth, content of parent-child sexual communication chiefly centre on admonitions against premarital sex; fifth, mothers discuss more sexual topics with the adolescent children than fathers. Sixth, discussion about contraceptive with adolescents is a topic which majority of households in the state avoid. Lastly, many parents still have inhibitions discussing sex-related issues with adolescents. There's need for interventions that target parents enlightenment and education and addressing cultural norms that impede parent-child sexual conversations; in order to  reposition families for parent-child communication that is open, receptive, sequential and time sensitive; conversations about sexual development and decision-making that enhance adolescent sexual and reproductive health.